Macroscopic Fungi Species in Kelimutu National Park, East Nusa Tenggara - Ridwan, Ridwan Fauzi; Hidayat, Muhamad Yusup Hidayat; Grace, Grace Serepina Saragih (Forestry Department, University of Muhammadiyah Makassar, 2018)
This study aims to identify macroscopic fungi species in Kelimutu National Park. The method used in this study was a combination of Visual Encounter Survey method in 5 tracking lines at altitude between 1,000 - 1,700 meters above sea level. Based on the results of the survey, there were 46 species of macroscopic fungi from 23 families in Kelimutu National Park. Some species of macroscopic fungi have the potential to be cultivated as food and medicinal ingredients. The existence of this macroscopic fungus has also given a special characteristic of Kelimutu because it only grows at an altitude between ± 1,045 - 1,616 meters above sea level.